Experiences of the treatments for the mandibular angle fracture - TANAKA, Youichi; OKA, Masuichiro; KAWANO, Yoshiharu; KURIYAMA, Kanji; ABE, Kihachiro; WAKAMORI, Minoru; KAJIOKA, Shunichi; KATSUYAMA, Hideaki; YOSHIDA, Atsuya; TAKENOSITA, Yasuharu (Japanese Journal of Oral and Maxillofacial Surgery, 1988)
Mandibular fracture treatment occupies a large part of oral surgery in hospital practice, yet much confusion exists in certain basic principles of treatment. Mandibular angle is known to be one of the most fractured areas in oral surgery because of its configuration and the common fracturing vectors. One big problem exists in dealing with teeth on the fracture line. Some authors consider any fracture through the alveolar socket or the crypt of an impacted tooth as a “complicated” fracture and say that the involved teeth even though uninjured should be extracted promptly because they may be the cause of complications such as nonuion, osteomyelitis, cellulitis or abscess formation. On the other hand, it is suggested that with the use of antibiotics and the application of stable fixation appliances, most clinically intact teeth in the line of mandibular fracture can be retained. From 1978 to MAY 1987, we treated 57 cases of mandibular angle fractures and analyzed the data with special reference to third molar teeth on the fracture line, types of fracture line, and way of approach and treatment. The majority of cases consisted of males (51/57, 89.5%), and were between 10 and 20 years old (68%). Some researchers mentionend that treatment for third molar teeth on the fracture line, but it is rare. So we considered this matter in more details. We, furthermore, examined fracture displacements of fragments, and so on.